Analisis Perilaku Remaja Yang Beresiko Mengalami Anemia - Sholihin; Lestari, Wina Eka; Putri, Novita Surya (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: Anaemia is a common health problem in society, especially among adolescents, and is often found in developing countries, including Indonesia. Anaemia in adolescents is caused by lifestyle factors, namely the habit of drinking coffee, sleep patterns, eating habits, and a lack of knowledge regarding the consumption of Iron Folic Acid (IFA) supplements. This study aimed to identify the behaviours of adolescents at risk of experiencing anaemia. Methods: This was qualitative research with a narrative approach. The data collection technique used was in-depth interviews with participant selection through purposive sampling, resulting in 6 participants who met the inclusion criteria. Data validation was conducted using member checking, and the data were analyzed using Burke's pentadic dramatism. Results: The results of the study found that most female adolescents had a lack of knowledge about anaemia. The factors causing anaemia included a lack of understanding of the benefits of consuming iron supplements, poor eating habits, inadequate sleep patterns, and heavy menstruation. The school's support in reducing the risk of anaemia includes the routine distribution of iron supplements every Friday through the active role of the Youth Red Cross (YRC) students. Support from family and peers is a driving factor in reducing the risk of anaemia. Conclusion: Female adolescents can be more diligent in taking iron supplements, checking their health, and adopting a healthier lifestyle to prevent anaemia.